Prinsip Epistemologi Islam pada Sekolah Islam Terpadu - Hidayat, Amirul; Herwina Bahar (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The principles of Islamic Epistemology are an important foundation in education at Integrated Islamic Schools. This article explores the concept and application of Islamic epistemological principles in an educational context. This principle guides curriculum development, teaching methods, and learning evaluation that are rooted in Islamic values. By considering the sources, processes and boundaries of knowledge from an Islamic perspective, these schools integrate religious teachings with learning, enriching students' experiences and strengthening their religious identity. This article highlights the importance of Islamic epistemological principles in understanding the relationship between science and religion and how their application improves education in Integrated Islamic Schools.